Growing Green: Menanamkan Kebiasaan Hidup Berkelanjutan Pada Anak Di Lembaga Pendidikan Anak Usia Dini - Koenarso, Dyah Ageng Pramesty (Institut Agama Islam Negeri Metro, 2023)
This article aims to understand how early childhood education can play a role in instilling sustainable living habits. The subject matter includes identifying effective strategies in incorporating sustainability aspects into the curriculum and daily activities in early childhood education institutions in Banjarmasin City. The research method adopted a qualitative approach with field research. The research was conducted in several early childhood education institutions that have implemented a sustainable approach. The research subjects included educators and young children. Data were collected through participatory observation, interviews and document analysis. The results show that experiential approaches and collaborative learning are effective in instilling sustainable living habits in early childhood. The conclusion emphasizes the need to integrate the concept of sustainability in the early childhood education curriculum. The implications of this research include strengthening the role of educational institutions in shaping young people who care about the environment and encouraging the adoption of educational policies that support sustainability goals.